SISTEM INFORMASI LABORATORIUM KOMPUTER UKRIDA - Septianto, Andy; Purba, Florensa Rosani (Teknik dan Ilmu Komputer, 2012)
In order to improve the laboratory user services, a system that can work quickly and efficiently is needed. The laboratory information system is one that can be used to simplify the laboratory management. The system can also be accessed via network so that the service can be done easily and quickly by the user.ÃÂ Keywords:ÃÂ information system, PHP, website